Temperature rises during tooth bleaching with different light-curing units - Özyılmaz, Özgün Yusuf; Yavuz, Tevfik; Sarı, Tu?rul; Aykent, Filiz; Öztürk, Atiye Nilgün (Taylor and Francis, 2015)
The aim of this study was to evaluate the influence of three different light-curing units on the temperature rise induced in the pulpal cavity, when bleached with 35% hydrogen peroxide (HP). Forty extracted maxillary central incisors were randomly divided into four groups according to photoactivation procedure (n=10). Whiteness HP (WHP) bleaching agent which contains 35% HP bleach was placed on the facial tooth surface and no photoactivation device was used (control); an blue light-emitting diode (LED, 40s), a diode laser (4W, Continous mode, 20s), and Nd:YAG laser (4W, 60Hz frequency, 20s). Temperature rise in the pulpal chamber was measured with a J-type thermocouple wire that was connected to a data logger before and immediately after each 20-40s application. One tooth of each group was selected for scanning electron microscope analysis. Data were analyzed using one-way ANOVA followed by the Games Howell post hoc test at a preset alpha of 0.05. One-way ANOVA revealed that there was a significant difference among the light-curing units (p<0.05) and between control group and light-curing units (p<0.05). The Nd:YAG induced significantly, which resulted in higher temperature increase than other light-curing units (10.7 degrees C). The LED unit produced the lowest temperature changes (3.2 degrees C) among the light-curing units. The presence of the bleaching gel did not cause a temperature increase in control group (0 degrees C). The results suggested that using light-curing units caused temperature changes in the intrapulpal cavity during tooth bleaching. The use of LED will be more safer for pulpal health when assisted with WHP bleaching gel.
WOS: 000354532700005
Keywords: Light-Curing Units; Laser; Thermocouple; Bleaching; Pulpal Health